Pengaruh Bauran Pemasaran terhadap Minat Nasabah dalam Menabung: Studi Kasus pada PT. BPRS Magetan - Daffa Fadhillah Burhanudin; Ach. Yasin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the results of research on the influence of the marketing mix on customer interest in savings products at PT. BPRS Magetan. This research used descriptive quantitative methods using a sample of 103 savings product customers as respondents. The distribution of questionnaires was carried out using a Likert scale on variables in the marketing mix, namely, product, price, place, promotion, people, process and physical evidence. This research uses multiple linear regression analysis using instrument data tests, classical assumption tests and hypothesis tests using the t test, f test and r2. The results of this research explain that partially the product, price, place, promotion and people variables have a positive and significant influence on customer interest in saving, while the process and physical evidence variables do not have a positive and insignificant influence on the customer interest variable in saving. Then simultaneously the variables product, price, place, promotion, people, process and physical evidence have a positive and significant influence on customer interest in saving. The results of the coefficient of determination test (R Square) showed that product, price, place, promotion, people, process and physical evidence had a simultaneous influence of 86.5% on customer interest in saving on PT. BPRS Magetan.